Efforts to Prevent Juvenile Delinquency from a Juridical and Psychological Perspective at Vocational High Schools (SMK) in Lubuklinggau - Alexander, Ongky; Amiruddin, Faizul; Supriadi; Arfaizar, Januariansyah; Anwar, Syaiful (Teumulong: Journal of Community Service, 2024)
This study examines efforts to address juvenile delinquency from both a legal and psychological perspective in vocational high schools (SMK) in Lubuklinggau. The study utilizes a qualitative approach, including case studies, surveys, interviews, and document analysis. The research aims to provide a comprehensive understanding of juvenile delinquency and inform the development of appropriate interventions. The findings highlight the importance of collaboration among parents, educational institutions, communities, and child protection agencies in preventing and addressing juvenile delinquency. From a legal perspective, the research emphasizes the need for a rehabilitative approach that considers adolescents' age, development, and capacity. From a psychological perspective, the study underscores the significance of understanding emotional development and identity exploration in teenagers and implementing preventive and intervention strategies. The research concludes that a comprehensive approach, integrating legal and psychological perspectives, is necessary to tackle juvenile delinquency in vocational high schools in Lubuklinggau effectively.